Shaping ability of ProTaper Ultimate and BlueShaper in mandibular molars: a micro-CT evaluation - Greco, Katia; Iacono, Francesco; Montagna, Francesco; Esposito Corcione, Carola; Paolone, Gaetano; Gherlone, Enrico; Cantatore, Giuseppe (Frontiers in Materials, 2024)
Aim: The study aimed to evaluate the shaping characteristics of ProTaper Ultimate (Dentsply Sirona) and BlueShaper (Zarc4Endo) using microcomputed tomographic imaging technology (micro-CT). Methods: Thirty mesial and distal canals of extracted second mandibular molars with similar anatomy were selected and scanned pre- and postoperatively by micro-CT scanning (SkyScan 1172, Bruker micro-CT) with a voxel size of 11 μm and shaped with two different procedures: ProTaper Ultimate (Group 1: n = 15) and BlueShaper (Group 2: n = 15) were used following the manufacturer’s recommendations up to final 30 apical size. Irrigation was ensured in all groups with 5.25% NaOCl and 10% EDTA during instrumentation. Canal transportation, the volume of removed dentin, and area of untreated surface were matched with preoperative values with Bruker CT Analyser (Bruker micro-CT). Data were statistically analyzed using Student’s t-test. Results: No significant differences were observed between Group 1 and Group 2 in terms of canal transportation, volume of removed dentin, and untreated surfaces. A significant difference (p < 0.05) in the amount of untreated surfaces was found between the mesial and distal canals in both groups. Conclusion: Shaping procedures with both ProTaper Ultimate and BlueShaper demonstrated similar canal enlargement volumes and similar canal transportation without evidence of significant preparation errors. Nevertheless, a high amount of untreated surface was reported for both systems, particularly in distal canals.